Anti‐allergic action of anti‐malarial drug artesunate in experimental mast cell‐mediated anaphylactic models. Issue 2 (18th December 2012) - Cheng, C.; Ng, D. S. W.; Chan, T. K.; Guan, S. P.; Ho, W. E.; Koh, A. H. M.; Bian, J. S.; Lau, H. Y. A.; Wong, W. S. F.
Abstract Background Allergy is an acquired hypersensitivity reaction of the immune system mediated by cross‐linking of allergen‐specific IgE‐bound high‐affinity IgE receptors, leading to immediate mast cell degranulation. Artesunate is a semi‐synthetic derivative of artemisinin, an active component of the medicinal plant Artemisia annua. Artesunate is a clinically effective anti‐malarial drug and has recently been shown to attenuate allergic asthma in mouse models. This study investigated potential anti‐allergic effects of artesunate in animal models of IgE‐dependent anaphylaxis. Methods Anti‐allergic actions of artesunate were evaluated in passive cutaneous anaphylaxis and passive systemic anaphylaxis mouse models, and in ovalbumin‐induced contraction of bronchial rings isolated from sensitized guinea pigs. Direct mast cell‐stabilizing effect of artesunate was examined in RBL‐2H3 mast cell line and in mature human cultured mast cells. Anti‐allergic signaling mechanisms of action of artesunate in mast cells were also investigated. Results Artesunate prevented IgE‐mediated cutaneous vascular hyperpermeability, hypothermia, elevation in plasma histamine level, and tracheal tissue mast cell degranulation in mice in a dose‐dependent manner. In addition, artesunate suppressed ovalbumin‐mediated guinea pig bronchial smooth muscle contraction. Furthermore, artesunate concentration‐dependently blocked IgE‐mediated degranulation of RBL‐2H3 mast cells and human culture mast cells. Artesunate was found to inhibit IgE‐induced Syk and PLCγ1 phosphorylation, production of IP3, and rise in cytosolic Ca+2 level in mast cells. Conclusions We report here for the first time that artesunate possesses anti‐allergic activity by blocking IgE‐induced mast cell degranulation, providing a foundation for developing artesunate for the treatment of allergic asthma and other mast cell‐mediated allergic disorders.